Vinyl acetate synthesis method, vinyl acetate synthesis catalyst and vinyl acetate preparation method
By using a support to support the combination of Pd, Group IB metal and alkali metal acetate in the vinyl acetate catalyst, the Pd2+ state and the reaction conditions are controlled, and the problems of high impurity content and high reaction temperature in the prior art are solved, and the efficient and low impurity production of vinyl acetate is achieved.
Patent Information
- Application Number
- CN202311292537.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-10-08
AI Technical Summary
The existing vinyl acetate catalyst has a high impurity content and a high reaction temperature, which affects product quality and production efficiency.
The catalyst supported by the carrier Pd, Group IB metal and alkali metal acetate was used to control the content of the Pd2+ state through X-ray photoelectron energy spectrum (XPS), optimize the composition of the catalyst and the program to warm up the surface reaction process, reduce the reaction temperature and reduce the impurity content of ethylene diacetate.
It significantly reduces the impurity content of ethylene acetate in the product, reduces the reaction temperature, and improves the production efficiency and product quality of ethylene acetate.
Smart Images

Figure BDA0004481949000000131
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for synthesizing vinyl acetate by an ethylene process and a preparation method thereof, and a method for synthesizing vinyl acetate. Background Art
[0002] At present, the main method for producing vinyl acetate is to use ethylene, oxygen and acetic acid as raw materials, palladium-gold-potassium acetate / silicon dioxide as catalyst, and produce vinyl acetate, water and by-product carbon dioxide through gas phase catalytic reaction. It also produces trace amounts of ethyl acetate, acetaldehyde and other acetoxylated products.
[0003] Vinyl acetate, also known as vinyl acetate or vinyl acetate, is a colorless, sweet and highly flammable liquid that can be dissolved in alcohols, benzene, ethers, acetone, and slightly soluble in water. Vinyl acetate is the precursor of polyvinyl acetate and ethylene-vinyl acetate copolymer, and is an important industrial polymer. Vinyl acetate can be used as an adhesive, a raw material for synthesizing vinylon as white glue, and producing coatings, etc. It has broad development space in the chemical field.
[0004] US3743607 discloses a catalyst containing palladium, gold and alkali metal acetate. The catalyst is prepared by the following steps: impregnating a carrier such as silicic acid, alumina, silicate or aluminum phosphate with an aqueous solution of a palladium salt and a gold salt; and evaporating the resulting mixture to dryness. This method contains a high amount of impurities. Summary of the invention
[0005] The object of the present invention is to provide a vinyl acetate catalyst which can significantly reduce the impurity content of ethylene diacetate in the product and can reduce the reaction temperature.
[0006] In the present invention, Pd 2+ / (Pd 0 +Pd 2+ The mass ratio of Pd and Pd is calculated by using the peak area of XPS. 0 With Pd 2+ The amount.
[0007] In the present invention, the composition of each substance in the catalyst is calculated based on the input materials.
[0008] The present invention provides a catalyst for synthesizing vinyl acetate by ethylene process, comprising a carrier and Pd, IB group metal and alkali metal acetate loaded on the carrier, wherein the X-ray photoelectron spectrum (XPS) of the catalyst shows that Pd 2+ The content of the catalyst in the state accounts for 10% to 45% of the total Pd element content, preferably 15-42%; the optimal reaction temperature point in the programmed temperature surface reaction process TPSR of the catalyst is 125 to 135°C. 2+ / (Pd 0+Pd 2+ ) mass ratio characteristics, can significantly reduce the impurity content of ethylene diacetate in the product.
[0009] In the present invention, the Group IB metal in the catalyst mainly exists in the form of a single substance.
[0010] In the present invention, Pd exists in the form of a simple substance and an oxide.
[0011] According to a preferred embodiment of the present invention, in the catalyst, the total Pd content, calculated as element, is 1 to 12 g / L, preferably 2 to 5 g / L, for example, 2.1 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L, 2.5 g / L, 2.6 g / L, 2.7 g / L, 2.8 g / L, 2.9 g / L, 3 g / L, 3.1 g / L, 3.2 g / L, 3.3 g / L, 3.4 g / L, 3.5 g / L, 3.6 g / L, 3.7 g / L, 3.8 g / L, 3.9 g / L, 4 g / L, 4.1 g / L, 4.2 g / L, 4.3 g / L, 4.4 g / L, 4.5 g / L, 4.6 g / L, 4.7 g / L, 4.8 g / L, 4.9 g / L, and 5 g / L. This can significantly reduce the impurity content of ethylene diacetate in the product.
[0012] According to a preferred embodiment of the present invention, the amount of Group IB metal in the catalyst, calculated as element, is 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L, for example 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L. This can significantly reduce the impurity content of ethylene diacetate in the product.
[0013] According to a preferred embodiment of the present invention, the content of alkali metal acetate is 10-100 g / L, preferably 20-40 g / L, for example 20 g / L, 30 g / L, 40 g / L, thereby significantly reducing the impurity content of ethylene diacetate in the product.
[0014] According to a preferred embodiment of the present invention, all Group IB metals can be used in the present invention. For the present invention, the Group IB metal is preferably Au and / or Cu, preferably Au. This can significantly reduce the impurity content of ethylene diacetate in the product.
[0015] According to a preferred embodiment of the present invention, the alkali metal element is selected from one or more of Li, Na, K, Rb, Cs, and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; thereby, the impurity content of ethylene diacetate in the product can be significantly reduced.
[0016] In the present invention, there is no special requirement for the carrier, and the commonly used carriers in the art can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, the carrier is selected from one or more of silicon oxide and aluminum oxide. According to a preferred embodiment of the present invention, preferably, the carrier is selected from spherical silicon dioxide, and preferably the diameter of the spherical silicon dioxide is 2-8 mm, and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g. The diameter of spherical silica in the present invention is 5mm and the specific surface area is 175m 2 / g, pore volume is 0.8cm 3 / g is used as an example to illustrate the advantages of the present invention, but the present invention is not limited to this.
[0017] The catalysts having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to the present invention, a preparation method of a catalyst for synthesizing vinyl acetate by ethylene process is provided, which method comprises: (a) immersing a catalyst support source in an N,N-methylenebisacrylamide solution, and drying to obtain a precursor I'; then immersing it in a solution containing a Pd source and an IB group metal source, and drying to obtain a precursor I;
[0018] (b) mixing and contacting the precursor I with a solution of a basic compound, and drying to obtain the precursor II;
[0019] (c) reducing the precursor II with a reducing agent, washing with water, and drying to obtain the precursor III;
[0020] (d) immersing the precursor III in a solution containing a Pd source and drying to prepare the precursor IV;
[0021] (e) impregnating the precursor IV with alkali metal acetate and drying to obtain a finished catalyst.
[0022] According to a preferred embodiment of the present invention, the optimal reaction temperature point in the temperature programmed surface reaction process TPSR of the prepared catalyst is 125-135°C.
[0023] According to a preferred embodiment of the present invention, the X-ray photoelectron spectroscopy (XPS) of the prepared catalyst shows that Pd 2+ The content of the Pd state accounts for 10% to 45% of the total Pd element content, preferably 15-42%; thereby, the impurity content of ethylene diacetate in the product can be significantly reduced.
[0024] According to a preferred embodiment of the present invention, in the prepared catalyst, the total Pd content, calculated as element, is 1 to 12 g / L, preferably 2 to 5 g / L; thereby, the impurity content of ethylene diacetate in the product can be significantly reduced.
[0025] According to a preferred embodiment of the present invention, in the prepared catalyst, the amount of Group IB metal, calculated as element, is 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L; thereby, the impurity content of ethylene diacetate in the product can be significantly reduced.
[0026] According to a preferred embodiment of the present invention, the content of alkali metal acetate in the prepared catalyst is 10-100 g / L, preferably 20-40 g / L, thereby significantly reducing the impurity content of ethylene diacetate in the product.
[0027] According to a preferred embodiment of the present invention, all Group IB metals can be used in the present invention. According to a preferred embodiment of the present invention, the Group IB metal is Au and / or Cu, preferably Au. This can significantly reduce the impurity content of ethylene diacetate in the product.
[0028] According to a preferred embodiment of the present invention, the alkali metal element is selected from one or more of Li, Na, K, Rb, Cs, and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate.
[0029] According to a preferred embodiment of the present invention, the concentration of the N,N-methylenebisacrylamide solution is 0.1-1.0 g / L.
[0030] According to a preferred embodiment of the present invention, the solvent of the N,N-methylenebisacrylamide solution is one or both of water and ethanol.
[0031] In the present invention, there is no special requirement for the carrier source, and the commonly used carrier sources in the art can achieve the purpose of the present invention. The present invention has no special requirements for this. The carrier source is selected from one or more of silicon dioxide and aluminum oxide; preferably, the carrier source is selected from spherical silicon dioxide, and preferably the diameter of the spherical silicon dioxide is 2-8 mm, and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
[0032] In the present invention, the alkaline compound can be selected from a wide range of types. According to a preferred embodiment of the present invention, in step (b), the alkaline compound includes but is not limited to one or more of sodium silicate and sodium hydroxide.
[0033] According to a preferred embodiment of the present invention, in step (c), the reducing agent includes but is not limited to one or more of hydrazine hydrate and sodium citrate.
[0034] According to a preferred embodiment of the present invention, the conditions in step (a) include: the conditions for immersing the catalyst support source in the N,N-methylenebisacrylamide solution include: the ratio of the volume of the N,N-methylenebisacrylamide solution to the volume of the support is 1-1.5:1.
[0035] According to a preferred embodiment of the present invention, the conditions in step (a) include: a solid-liquid volume ratio of 1:1-1:1.2, a Pd content of 1 to 12 g / L, preferably 2 to 3 g / L, in the solution containing a Pd source and a Group IB metal source, calculated as an element; and a Group IB metal content of 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L.
[0036] According to a preferred embodiment of the present invention, the conditions in step (b) include: the volume ratio of the solution of the basic compound to the carrier is 0.05 to 0.5, preferably 0.07 to 0.1.
[0037] According to a preferred embodiment of the present invention, the conditions in step (b) include: the concentration of the solution of the basic compound is 10-30% by weight.
[0038] In the present invention, there are no special requirements for the reduction, water washing and drying conditions. Common reduction, water washing and drying conditions can be used in the present invention. According to a preferred embodiment of the present invention, the conditions in step (c) include: reduction time of 1-10 hours; water washing time of 1-20 hours; drying temperature of 60-100° C.; drying time of 1-10 hours.
[0039] According to a preferred embodiment of the present invention, the conditions in step (d) include: a solid-liquid volume ratio of 1:1-1.2, and a Pd content in the solution of 0.5-2 g / L.
[0040] According to a preferred embodiment of the present invention, preferably, step (d) is carried out in the presence of acetic acid, and the amount of acetic acid used is 1-10 g / L solid, preferably 5-8 g / L solid.
[0041] According to a preferred embodiment of the present invention, the conditions in step (e) include: drying temperature of 60-100° C.; and drying time of 1-10 hours.
[0042] In the present invention, in steps (a) to (e), the process is allowed to stand as required in order to allow the solid and the liquid to fully contact each other.
[0043] In the present invention, step (a) can be optionally allowed to stand for 0.5-3 hours as required.
[0044] In the present invention, step (b) can be optionally allowed to stand for 12-24 hours as required.
[0045] In the present invention, step (c) can be optionally allowed to stand for 3-6 hours as required.
[0046] In the present invention, step (d) can be optionally allowed to stand for 3-6 hours as required.
[0047] In the present invention, step (e) can be optionally allowed to stand for 3-6 hours as required.
[0048] In the present invention, the purpose of drying is to remove liquid matter from the solid. Generally, the drying is performed so that the solid content is above 95wt%, and there is no special requirement for the technology.
[0049] The present invention provides a catalyst prepared by the preparation method of the present invention.
[0050] The present invention provides a method for synthesizing vinyl acetate. In the presence of a catalyst, raw gas for synthesizing vinyl acetate undergoes a gas-phase catalytic synthesis reaction. The catalyst includes the catalyst of the present invention.
[0051] According to a preferred embodiment of the present invention, the raw gas for synthesizing vinyl acetate includes oxygen, ethylene, nitrogen and acetic acid; preferably, the raw gas composition in a molar ratio is oxygen:ethylene:nitrogen:acetic acid=1:(5-7):(4-8):(1-2).
[0052] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: the reaction pressure is 0.5 to 0.9 MPa.
[0053] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: a reaction temperature of 130 to 200°C.
[0054] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: the raw gas volume space velocity is 1600 to 3000 hr -1 .
[0055] In the present invention, unless otherwise specified, the operation is carried out at room temperature.
[0056] In the present invention, unless otherwise specified, the solvent of the solution is water.
[0057] In the present invention, the content of each component in the catalyst is tested by: the content of elements in different valence states is represented by the peak area of the XPS spectrum, and the peak area ratio can represent the ratio of the content of elements in different valence states.
[0058] In the present invention, STY refers to the space-time yield of vinyl acetate, which is calculated as follows: STY (t / dm 3 )=86*ethylene consumption (mol / d)*1000 / catalyst dosage (m 3).
[0059] The catalyst with the characteristics of the present invention can reduce the reaction temperature and significantly reduce the impurity content of ethylene diacetate in the product. DETAILED DESCRIPTION
[0060] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0061] The advantages of the present invention are described in detail below by way of embodiments, but the present invention is not limited thereto.
[0062] Example 1
[0063] 1. Catalyst preparation
[0064] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in an ethanol solution of N, N-methylenebisacrylamide (wherein, the concentration of N, N-methylenebisacrylamide was 0.1 g / L; the ratio of the volume of the impregnation solution to the volume of the carrier was 1.5), and after being immersed for half an hour, it was dried to obtain a precursor I'; then it was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, and the solid-liquid volume ratio was 1:1.2, wherein the content of palladium (calculated as element, the same below) in the solution used was 2.75 g / L, and the content of gold (calculated as element, the same below) was 0.625 g / L, and it was allowed to stand for 3 hours. The drying conditions included: drying at 80°C for 30 minutes to prepare a catalyst precursor I;
[0065] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution); mixing well and letting stand for 24 hours, and then drying at 80° C. for 8 hours to obtain catalyst precursor II;
[0066] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0067] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 0.50 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0068] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0069] 2. Catalyst evaluation
[0070] The fixed bed reactor was used for evaluation, and the specific conditions were:
[0071] Catalyst filling volume: 40ml;
[0072] The composition of the reaction raw materials (by molar ratio): oxygen: ethylene: nitrogen: acetic acid = 1: 6.9: 7.0: 2.0;
[0073] Reaction raw material feed volume space velocity: 2020hr -1 ;
[0074] Reaction pressure: 0.7MPa;
[0075] Reaction temperature: 132°C;
[0076] Reaction time: 100hr;
[0077] The content of each component in the reaction product was analyzed by gas chromatography, and then the space-time yield of the catalyst was calculated.
[0078] For the convenience of comparison, the experimental results are listed in Table 1.
[0079] Example 2
[0080] 1. Catalyst preparation
[0081] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in an aqueous solution of N, N-methylenebisacrylamide (wherein, the concentration of N, N-methylenebisacrylamide was 1.0 g / L; the ratio of the volume of the impregnation solution to the volume of the carrier was 1.5), immersed for half an hour, dried and immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and allowed to stand for 3 hours. The drying conditions included: drying at 80°C for 30 minutes to prepare a catalyst precursor I;
[0082] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution); mixing well and letting stand for 24 hours, and then drying at 80° C. for 8 hours to obtain catalyst precursor II;
[0083] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0084] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 0.92 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0085] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0086] 2. Catalyst evaluation
[0087] The catalyst evaluation method was the same as in Example 1.
[0088] For the convenience of comparison, the experimental results are listed in Table 1.
[0089] Example 3
[0090] 1. Catalyst preparation
[0091] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in an aqueous solution of N, N-methylenebisacrylamide (wherein the concentration of N, N-methylenebisacrylamide was 0.6 g / L; the ratio of the volume of the impregnation solution to the volume of the carrier was 1.5), immersed for half an hour, and then dried; immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, and allowed to stand for 3 hours, and the content of palladium in the solution used was calculated according to a solid-liquid volume ratio of 1:1.2, and the content of gold was 0.625 g / L, and the drying conditions included: drying at 80°C for 30 minutes to prepare a catalyst precursor I;
[0092] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution); mixing well and letting stand for 24 hours, and then drying at 80° C. for 8 hours to obtain catalyst precursor II;
[0093] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0094] (d) immersing the catalyst precursor III in an aqueous solution of chloropalladic acid, wherein the solid-liquid volume ratio is 1:1.2, wherein the palladium content in the solution used is 1.18 g / L, mixing well, standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0095] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0096] 2. Catalyst evaluation
[0097] The catalyst evaluation method was the same as in Example 1.
[0098] For the convenience of comparison, the experimental results are listed in Table 1.
[0099] Example 4
[0100] 1. Catalyst preparation
[0101] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in an aqueous solution of N, N-methylenebisacrylamide (wherein the concentration of N, N-methylenebisacrylamide was 1.0 g / L; the ratio of the volume of the impregnation solution to the volume of the carrier was 1.5), immersed for half an hour, and then dried; then immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and allowed to stand for 3 hours. The drying conditions included: drying at 80°C for 30 minutes to prepare a catalyst precursor I;
[0102] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution); mixing well and letting stand for 24 hours, and then drying at 80° C. for 8 hours to obtain catalyst precursor II;
[0103] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0104] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 2.0 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0105] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0106] 2. Catalyst evaluation
[0107] The catalyst evaluation method was the same as in Example 1.
[0108] For the convenience of comparison, the experimental results are listed in Table 1.
[0109] Example 5
[0110] The method of Example 1 was followed, except that 6 g of acetic acid was added to the solution in step (d).
[0111] Comparative Example 1
[0112] 1. Catalyst preparation
[0113] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and the drying conditions included: drying at 80° C. for 30 minutes to prepare a catalyst precursor I;
[0114] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0115] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0116] (d) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0117] 2. Catalyst evaluation
[0118] The catalyst evaluation method was the same as in Example 1.
[0119] For the convenience of comparison, the experimental results are listed in Table 1.
[0120] Comparative Example 2
[0121] 1. Catalyst preparation
[0122] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 1g / L, and the content of gold was 0.1g / L, and the drying conditions included: drying at 80°C for 30 minutes to prepare a catalyst precursor I;
[0123] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0124] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0125] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 0.92 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0126] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0127] 2. Catalyst evaluation
[0128] The catalyst evaluation method was the same as in Example 1.
[0129] For the convenience of comparison, the experimental results are listed in Table 1.
[0130] Comparative Example 3
[0131] 1. Catalyst preparation
[0132] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 12 g / L, and the content of gold was 10 g / L, and the drying conditions included: drying at 80° C. for 30 minutes to prepare a catalyst precursor I;
[0133] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0134] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0135] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 0.92 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0136] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0137] 2. Catalyst evaluation
[0138] The catalyst evaluation method was the same as in Example 1.
[0139] For the convenience of comparison, the experimental results are listed in Table 1.
[0140] Table 1
[0141]
[0142] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for synthesizing vinyl acetate from ethylene, characterized in that: The catalyst comprises a carrier and Pd, IB group metal and alkali metal acetate loaded on the carrier, wherein the X-ray photoelectron spectrum of the catalyst shows that Pd 2+ The content of the catalyst in the programmed temperature surface reaction process TPSR is 125-135°C.
2. The catalyst according to claim 1, wherein X-ray photoelectron spectroscopy of the catalyst showed that Pd 2+ The content of the state is 15-42% of the total Pd element content; and / or The catalyst contains 1 to 12 g / L of total Pd, preferably 2 to 5 g / L, calculated as the element; and / or The catalyst contains 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L, of Group IB metal, calculated as the element; and / or The content of alkali metal acetate in the catalyst is 10 to 100 g / L, preferably 20 to 40 g / L.
3. The catalyst according to claim 1 or 2, wherein The IB group metal is Au and / or Cu, preferably Au; and / or The alkali metal element is selected from one or more of Li, Na, K, Rb, Cs and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; and / or The carrier is selected from one or more of silicon oxide and aluminum oxide; Preferably, the carrier is selected from spherical silica, preferably the diameter of the spherical silica is 2-8 mm and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
4. A method for preparing a catalyst for synthesizing vinyl acetate by ethylene process, characterized in that: The method includes: (a) immersing a catalyst support source in an N,N-methylenebisacrylamide solution and drying to obtain a precursor I'; then immersing the catalyst support source in a solution containing a Pd source and a Group IB metal source and drying to obtain a precursor I; (b) mixing the precursor I with a solution of a basic compound, and drying to obtain the precursor II; (c) reducing the precursor II with a reducing agent, washing with water, and drying to obtain the precursor III; (d) immersing the precursor III in a solution containing a Pd source and drying to prepare the precursor IV; (e) impregnating the precursor IV with alkali metal acetate and drying to obtain a finished catalyst.
5. The preparation method according to claim 4, wherein The optimal reaction temperature point in the temperature-programmed surface reaction process TPSR of the prepared catalyst is 125-135°C; X-ray photoelectron spectroscopy of the prepared catalyst showed that Pd 2+ The content of the Pd state accounts for 10% to 45% of the total Pd element content, preferably 15-42%; and / or In the prepared catalyst, the total Pd content is 1 to 12 g / L, preferably 2 to 5 g / L, calculated as the element; and / or In the prepared catalyst, the content of Group IB metal is 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L, calculated as the element; and / or In the prepared catalyst, the content of alkali metal acetate is 10-100 g / L, preferably 20-40 g / L.
6. The preparation method according to claim 4 or 5, wherein: The Group IB metal is Au and / or Cu, preferably Au; and / or The alkali metal element is selected from one or more of Li, Na, K, Rb, Cs and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; and / or In step (a), the carrier source is selected from one or more of silicon dioxide and aluminum oxide; The concentration of the N,N-methylenebisacrylamide solution is 0.1-1.0 g / L; and / or The solvent of the N,N-methylenebisacrylamide solution is one or two of water and ethanol; and / or Preferably, the carrier source is selected from spherical silica, preferably the diameter of the spherical silica is 2-8 mm and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g; and / or In step (b), the alkaline compound is selected from one or more of sodium silicate and sodium hydroxide; and / or In step (c), the reducing agent is selected from one or more of hydrazine hydrate and sodium citrate.
7. The preparation method according to any one of claims 4 to 6, wherein: The conditions in step (a) include: The conditions for immersing the catalyst support source in the N,N-methylenebisacrylamide solution include: the ratio of the volume of the N,N-methylenebisacrylamide solution to the volume of the support is 1-1.5:1; and / or The conditions for immersing in a solution containing a Pd source and a group IB metal source include: a solid-liquid volume ratio of 1:1-1.2, a Pd content of 1 to 12 g / L, preferably 2 to 3 g / L, and a group IB metal content of 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L in the solution containing a Pd source and a group IB metal source, calculated as an element; and / or The conditions in step (b) include: the concentration of the alkaline compound solution is 10-30% by weight, and the volume ratio of the alkaline compound solution to the carrier is 0.05-0.5, preferably 0.07-0.1; The conditions in step (d) include: a solid-liquid volume ratio of 1:1-1.2, and a Pd content in the solution of 0.5-2 g / L; Preferably, step (d) is carried out in the presence of acetic acid, and the amount of acetic acid used is 1-10 g / L solid, preferably 5-8 g / L solid.
8. The catalyst prepared by the preparation method according to any one of claims 4 to 7.
9. A method for synthesizing vinyl acetate, wherein the raw material gas for synthesizing vinyl acetate is subjected to a gas phase catalytic synthesis reaction in the presence of a catalyst, characterized in that: The catalyst comprises the catalyst according to any one of claims 1 to 3 and 8.
10. The synthesis method according to claim 9, wherein The raw gas for synthesizing vinyl acetate includes oxygen, ethylene, nitrogen and acetic acid; preferably, In terms of molar ratio, the molar ratio of oxygen, ethylene, nitrogen and acetic acid is 1:(5-7):(4-8):(1-2); and / or The conditions for the gas phase catalytic synthesis reaction include: The reaction pressure is 0.5-0.9 MPa, and / or The reaction temperature is 130-200°C, and / or The raw gas volume space velocity is 1600~3000hr -1 .
Citation Information
Patent Citations
Palladium-gold catalyst
US3743607A
Gas adsorbent, preparation method and applications thereof
CN110856815A
Ethylene method vinyl acetate catalyst and preparation method thereof
CN113751077A
Catalyst for synthesizing vinyl acetate by using ethylene method and preparation method of catalyst
CN114073986A
Vinyl acetate synthesis method
CN115246771A